PO.3.69 A case of late onset of primary antiphospholipid syndrome. (27th September 2022) - Salvucci, S; Manfredi, L; Gamba, L; Montozzi, G; Santangeli, R; Moroncini, G
Abstract : Purpose: Antiphospholipid syndrome (APS) usually affects young patients and is rarely described in the elderly. Here, we present a case of late-onset of triple-positive primary APS characterized by recurrent thrombotic events. Methods: In November 2019, an 80-year-old man presented the first deep vein thrombosis in his left leg. He received fondaparinux treatment for one year, but the thrombosis relapsed one month after stopping treatment. The search for thrombophilic causes has shown positivity for antiphospholipid antibodies (LAC, anticardiolipin, and anti-beta2 glycoprotein I IgM at high titres). In addition, the patient underwent first-level diagnostics and endoscopic examinations excluding other immunological causes, infections and malignancy. A diagnosis of primary APS was made and the warfarin therapy started with a range of INR between 2 and 3. In November 2021, the patient was brought to our attention following the recurrence of thrombosis of the deep iliac and femoral veins despite anticoagulant treatment. Laboratory tests confirmed the presence of triple high titre positivity of antiphospholipid antibodies and a total body CT scan confirmed the absence of suspected malignant lesions. Serological studies with a comprehensive autoimmunity panel for other autoimmune disorders were negative and an echocardiographic study ruled out the presence of cardiac involvement. Results: Although age has been demonstrated to be a risk factor for severe bleeding episodes in patients placed on long-term anticoagulation, we decided to start hydroxychloroquine and combination therapy with warfarin (INR range between 2.5 and 3.5) and low-dose aspirin according to EULAR recommendations, considering the patient's good clinical condition and absence of comorbidities. The patient was informed about the nature of the disease and the need for treatment with a high risk of bleeding. In December 2021, despite vaccination with two doses, he contracted COVID-19 infection and warfarin treatment was replaced with low molecular weight heparin at prophylactic dosage, but after some days he presented dyspnoea with desaturation. A lung CT scan showed bilateral pulmonary embolism, attributable to intercurrent viral infection and to APS (not completely controlled after warfarin withdrawal), and so clinicians decided to replace treatment with warfarin. After one month, patient had been discharged from hospital in good clinical health. Conclusions: Accurate diagnosis and treatment of late-onset APS represent a challenge due to the lack of knowledge of this disease in the elderly.